Influence of Workload and Coworker Support on the Emloyees”™ Performance at PT Mitra Kargo Indonesia - Aviadi, Khansa Zamaya; Farouk, Umar -; Indrasari, Febrina - (Politeknik Negeri Semarang, 2024)
In a competitive work environment, companies need to effectively monitor and manage employees”™ performance to achieve sustainable business success. Workload and coworker support are crucial factors that affect employees”™ performance. This study aims to analyze the impact of workload and coworker support on employees”™ performance at PT Mitra Kargo Indonesia, a freight forwarder company in Semarang. A quantitative approach was applied in this research, with data obtained from questionnaires.observations, and literature studies. The questionnaire used a semantic differential scale with scores ranging from 1 to 10. The research population included 38 employees of PT Mitra Kargo Indonesia, and the sampling method used was saturated sampling. Data analysis included classical assumption tests, multiple linear regression analysis, F-test, t-test, and coefficient of determination, all conducted using SPSS version 25. The results revealed that workload and coworker support significantly influence employees”™ performance, contributing a total of 61.4%. The remaining 38.6% of employees”™ performance is influenced by other variables not tested in this study.